A review of visual ethnography: Radiography viewed through a different lens. (October 2019) - O'Regan, T.; Robinson, L.; Newton-Hughes, A.; Strudwick, R.
Abstract: Introduction: The objective of this article is to provide a short review of the research methodology 'visual ethnography'. Method: The review article will provide a summary of the foundations of visual ethnography, outline the key debates and refer to some of the main authors working in this field. Results: Visual Ethnography is both a methodology and a method of research. It should be selected for research in radiography when research questions seek to focus upon aspects or elements of a culture. A research plan that is designed using a visual ethnographic approach should be flexible and take into account the requirements of the researcher and research participants. Visual methods of research include the use of various images, for example, photographs, collage, film or drawings. Visual methods are commonly employed together with interviews, conversations and observation. The approach enables researchers to generate new and unique insights into cultures. Conclusion: This review of visual ethnography provides background information that informs an introduction to the methodology. It demonstrates a methodology with the potential to explore culture and expand knowledge of radiography practice. Implications for practice: The authors suggest that for future studies visual ethnography is a methodology that can expand the paradigm of radiography research.